Penatalaksanaan Holistik Penyakit Pada Anak dengan Skabies Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Segala Mider - Amourisva, Assyiva Putri; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2024)
Scabies is a skin disease caused by the mite Sarcoptes scabei parasite, which causes itching that gets worse at night and can be transmitted through prolonged contact with sufferers. Factors that influence the prevalence of scabies are age, gender, poor hygiene, contact with sufferers, and also low knowledge about the disease. So that proper treatment is needed and carried out holistically with a family medicine approach to achieve therapeutic success. The purpose of writing this article is to apply of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient problem solving framework using a patient centered and family approach. This study is a case report. The data obtained are primary data obtained through autoanamnesis, alloanamnesis, physical examination, and home visits and secondary data obtained from the patient's medical record. Patient An. N, 15 years old, came with his mother with complaints of severe itching at night since a month ago, there were reddish nodules the size of pins appearing on the palms of his hands, then spreading to other areas. The patient is worried that it will get worse and interfere with activities. The patient was clinically diagnosed with scabies. Furthermore, management, intervention and evaluation are carried out. On evaluation, there were reduced complaints, patient knowledge about the disease increased, and changes in behavior in maintaining personal and environmental hygiene. After holistic and comprehensive management, patients experience an increase in knowledge about their disease. Complaints of itching and nodules in patients are reduced, patients and their families maintain personal and environmental hygiene.